رؤية الإسلام تجاه أدلجة العلم التجريبي المعاصر = Islamic view towards the ideologicalization of contemporary experimental science - Shukur, Ied Shukur; Ahmed Ali, Ahmed El-Mogtaba Bannga (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia., 2017)
يُناقش هذا البحث قضيَّة تنامي مخاوف الإنسانيَّة من أدلجة العلم التجريبي المعاصر، ويكشف عن حقيقة هواجسها ومبرّراتها الموضوعيَّة، وما آلت إليه من صيحات تُنادي بضرورة البحث عن مرجعيَّةٍ فكريَّةٍ حياديَّة عُليا، تقود العلم الحديث وتحدّد مساره، وتحصّنه من إيديولوجيَّات السياسة، وتحدّ من خضوعه لسلطة المال، وتُزواج آليَّاته بقيم الأخلاق. وعلى تسارع إيقاع تلكم المخاوف تتمحور إشكاليَّة البحث فتطرح أسئلتها التالية: ما حقيقة مخاوف المجتمع الدولي من تداعيات أدلجة العلم التجريبي المعاصر؟ وما السبيل إلى إيجاد مرجعيَّةٍ معرفيَّةٍ عُليا تتّسم بالحياد وتضمن تصحيح مسار العلم وتقود توجّهاته؟ وما مدى إمكانيَّة طرح الرؤية الإسلاميَّة كمرجعيَّة معرفيَّة تساهم في قيادة العلم الإنساني وتُحقِّق أهدافه المنشودة؟ ولبيان ذلك اعتمد الباحث على المنهجين: الاستقرائي في تتبُّع التحريرات المنبثقة من مخاوف أدلجة العلم الحديث، والتحليلي في دراسة الحلول المقترحة والمسارات التصحيحيَّة المقدَّمة، ومقارنتها برؤية الإسلام تجاه العلم، وقد بيَّن البحثُ أنَّ الرؤيةَ الإسلاميَّة تمثِّل حلَّاً ملائماً يضمن في حال تبنّيه تحرير العلم من كلّ إيديولوجيا؛ كونها تتكوَّن من خمسة ركائز تُحيل كلّ واحدة منها إلى الأخرى وتتضمَّنها بالضرورة، فتعالج خللاً أو تسدُّ ثغرةً تُفضي إلى أدلجة العلم التجريبي المعاصر. ******************************************************** This research discusses the human concern about the ideologicalization of contemporary experimental science, and reveals the real worries and substantive justifications of this concern, as well as some inquiries for the need to search for a higher neutral intellectual reference that determines the course of modern science and protects it from the control of different political ideologies as well as does not allow it to submit itself to the financial control and provides for it a moral-based mechanism. The problem raised by this research about the acceleration of these concerns arises the following questions: What is the truth of the concerns of the international community about the implications of the argument of contemporary experimental science? How to find a supreme knowledge authority that is neutral and ensures that the course of knowledge is guided? And the extent to which the Islamic vision can be presented as a reference knowledge that contributes to the leadership of human science and achieves its beneficial purpose for humanity? The research has shown that the Islamic vision is an appropriate solution that, if adopted, will ensure the freeing of science from every ideology; being that vision consists of five pillars complement each other, It addresses a gap that leads to the ideologicalization of contemporary experimental science.